PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR ILMIAH DAN PRESTASI BELAJAR SISWA (Studi pada Mata Pelajaran Matematika Siswa Kelas 5 SD Negeri 11 Merapi Barat Kecamatan Merapi Barat) - Indra Gandi (DIADIK, 2020)
Thisstudy aimstodescribetheapplicationofproblembasedlearningmodel to improvescientificthinking andstudents’achievement.Thisresearch usesclassroom actionresearchandquasi-experimentalmethods.Theresearchsubjectsare30students ofthefifthgradeofsemestertwoofthe2019/2020academicyearatSDNegeri11MerapiBarat.Forthequasi-experimentalsamplesare24studentsinclassV/Band24 studentsinclassV/CinMerapi Baratas thesecond  group.Datacollectionmethodsin thisstudyusedobservation sheets ofstudents'scientificthinkingandtestinstrumentsto measurestudents’achievement.Analysisofresearchdatausingdescriptivestatistics thatisaverage(mean).Analysisof theresultsofstudentlearningresearchbeforeand aftertheactionisanalyzedusingqualitatifandquantitatifdata.From theresultsofthe study,itshowsthattheapplicationof theproblembasedlearningmodelcanimprove scientificthinkingandstudents’achievementinmathematicssubjectofthefifthclass SDNegeri11Merapi Barat